2019
DOI: 10.1167/tvst.8.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Steady-State Visually Evoked Potentials Elicited by Multifrequency Pattern-Reversal Stimulation

Abstract: Purpose It has been shown that multifrequency stimulation with multifocal electroretinography can reduce recording time without a loss in signal-to-noise ratio. Here, we studied the applicability of multifrequency stimulations for steady-state visually evoked potential (VEP) recordings. Methods Multifrequency VEPs were recorded monocularly from 10 healthy subjects using pattern-reversal stimuli. The reversal frequency varied between 5 and 30 Hz. Pattern-reversal checker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…at about 10 Hz) [ 12 ] and should be chosen outside this frequency range. Preceding studies showed that a stimulus frequency of about 12 Hz, as used in the present student, gives optimal results [ 19 , 28 , 31 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…at about 10 Hz) [ 12 ] and should be chosen outside this frequency range. Preceding studies showed that a stimulus frequency of about 12 Hz, as used in the present student, gives optimal results [ 19 , 28 , 31 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…As in an earlier study [ 19 ], we used the ratio of signal amplitude at reversal frequency divided by the mean of two neighbouring frequencies for calculations of the SNR ratio [ 14 ]. Pilot studies showed that the use of two direct neighbouring frequencies for SNR calculation performed better than the inclusion of 4 or more [ 34 ] non-signal amplitudes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SSVEPs are obtained at a frequency of more than 3 Hz. Moreover, SSVEPs have several advantages over TVEPs [9], such as increased resistance to noise artifacts that inevitably occur during measurements due to skin potentials and myographic noise and ease of extraction from background noise [10,11]. Therefore, SSVEPs are widely used in the elds of visual perception and cognitive research in human medicine [9,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Visual evoked potentials (VEPs) are a tool to investigate the visual pathways up to the visual cortex [7]. Electro-encephalographic potentials provoked by visual stimulation are recorded from the visual cortex after passing the retinal and subcortical visual pathways [8,9]. It has been shown that the VEP shows glaucoma induced changes when chromatic stimuli are applied [3].…”
Section: Introductionmentioning
confidence: 99%